Perspectives on Challenges to Cell Therapy Development in Taiwan: Strengthening Evidential Standards and Ways Forward - Abolarinwa, Bilikis Aderonke; Shaw, Malissa Kay; Lee, Chung-Hsi (Frontiers in Bioengineering and Biotechnology, 2021)
Over the past years, the field of regenerative medicine and cell therapy has garnered much interest, extending beyond the bench to broader use and commercialization. These therapies undergo stringent regulatory oversight as a result of their complexities and potential risk across different jurisdictions. Taiwan’s government, with the aim of developing the country as a hub for regenerative medicine in Asia, enacted a dual track act to promote the development of regenerative and cell therapy products. This qualitative study used purposive sampling to recruit sixteen experts (Twelve respondents from medical institutions and four respondents from the industry) to understand their perspectives on one of the regulatory tracks which governs medical use of cell technologies and the challenges regarding its implementation. Semi-structured interviews were conducted, transcribed, coded and thematically analyzed. Three major themes emerged from the analysis: (1) Perceptions of the “Special Regulation for Cell Therapy” (2) Emerging issues and controversies on the medical use of cell technologies in private clinics, and (3) Challenges impeding the clinical innovation of cell technologies. As reported by the experts, it was clear that the special regulation for cell therapy was aimed at legalizing the clinical use of cell therapy in a similar fashion to an evidence-based pathway, to promote clinical innovation, ensure manufacturing consistency and improve oversight on cell-based therapies. Thus, the regulation addresses the issues of safety concerns, patient’s access and stem cell tourism. However, the limited approved cell techniques, quality control during cell processing, time and criteria used in evaluating applications in addition to the need to develop evidential standards for clinical evidence are some of the difficulties faced. Thus, policy interventions on funding, educational resources, training and regulatory clarity addressing these challenges may positively impact clinical innovation of cell therapy in Taiwan.